Analysis of pollen in honey samples in the district of Prayagraj, India - Mehdi, Jafar; Yadav, Ravi Kumar; Gupta, Anil Kumar (Current Botany, 2023)
The analysis of pollen grains found in honey, known as melissopalynology, reveals pertinent details about the pollen and nectar sources in a location where bees produce honey, allowing researchers to identify the honey’s geographical and botanical origins. To determine the significant source plants in the area, the present analysis is conducted on five samples of winter honey that were collected from Prayagraj’s urban localities (Dahi, Baksi, Sirsa, Soraon, and Phoolpur). The methodology recommended by the International Commission of Bee Botany (ICBB) was followed in this study. Analysis of 5 honey samples recorded a diversity of 31 pollen types and one fungal spore type. The majority of pollen grains recovered from honey samples belong to entomophilous taxa (66%), 25% of the pollen is from anemophilous taxa, and 9% from amphiphilous taxa. Four honey samples (S1, S2, S3, and S5) were found to be unifloral while the remaining samples (S4) were multi-floral. The field mustard i.e. Brassica campestris L. was the predominant pollen type. The secondary frequency class contained three different pollen types, while the minor and significant minor frequency classes contained 14 and 30, respectively. With respect to the frequency of occurrence of pollen types in honey samples, field mustard was found to be a very common pollen type as they were recovered from more than 50% of the collected honey samples. The various type of pollen and spores were also observed in collected honey samples.